Risks for human health related to the presence of pyrrolizidine alkaloids in honey, tea, herbal infusions and food supplements. (27th July 2017) - ,; Knutsen, Helle Katrine; Alexander, Jan; Barregård, Lars; Bignami, Margherita; Brüschweiler, Beat; Ceccatelli, Sandra; Cottrill, Bruce; Dinovi, Michael; Edler, Lutz; Grasl‐Kraupp, Bettina; Hogstrand, Christer; et al.
Abstract: EFSA was asked by the European Commission to deliver a scientific opinion on the risks for human health related to the presence of pyrrolizidine alkaloids (PAs) in honey, tea, herbal infusions and food supplements and to identify the PAs of relevance in the aforementioned food commodities and in other feed and food. PAs are a large group of toxins produced by different plant species. In 2011, the EFSA Panel on Contaminants in the Food Chain (CONTAM Panel) assessed the risks related to the presence of PAs in food and feed. Based on occurrence data limited to honey, the CONTAM Panel concluded that there was a possible health concern for those toddlers and children who are high consumers of honey. A new exposure assessment including new occurrence data was published by EFSA in 2016 and was used to update the risk characterisation. The CONTAM Panel established a new Reference Point of 237 μg/kg body weight per day to assess the carcinogenic risks of PAs, and concluded that there is a possible concern for human health related to the exposure to PAs, in particular for frequent and high consumers of tea and herbal infusions. The Panel noted that consumption of food supplements based on PA‐producing plants could result in exposure levels causing acute/short‐term toxicity. From the analysis of the available occurrence data, the CONTAM Panel identified a list of 17 PAs of relevance for monitoring in food and feed. The Panel recommended continuing the efforts to monitor the presence of PAs in food and feed, including the development of more sensitive and specific analytical methods. A recommendation was also issued on the generation of data to identify the toxic and carcinogenic potency of the PAs commonly found in food.